A method for preparing thermoplastic polyurethane with antistatic surface

CN119019740BActive Publication Date: 2025-02-11HUADA CHEM GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411504948.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-11
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

外部涂覆型常用的抗静电剂是季铵盐型表面活性剂,采用涂覆或者浸渍等方式使材料表面具有抗静电性,该工艺简单,操作方便,不受TPU制品形状的限制,但是制品表面抗静电剂会因为摩擦、洗涤而消失,耐久性较差

Benefits of technology

[0028] The present invention uses polyester-type glycol containing double bond structure to prepare thermoplastic polyurethane elastomers containing double bonds, and then prepares surface antistatic thermoplastic polyurethanes with surface antistatic treatment to achieve the purpose of surface antistatic modification. The surface resistivity of the thermoplastic polyurethane with antistatic surface can reach 2.3×10 8 Ω, reaches the antistatic level and has long-term durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of thermoplastic polyurethane elastomers, and relates to a method for preparing a thermoplastic polyurethane with antistatic surface, comprising the following steps: (1) preparing a thermoplastic polyurethane product by weight percentage from 35% to 70% polyester diol containing a double bond structure; 25% to 55% diisocyanate; 2% to 15% chain extender; 0.001% to 0.05% catalyst; 0.1% to 0.3% antioxidant; and 0.1% to 0.3% light stabilizer; and (2) subjecting the thermoplastic polyurethane product to surface antistatic treatment. The present invention prepares a thermoplastic polyurethane with antistatic surface, and achieves the purpose of surface antistatic modification. The surface resistivity of the thermoplastic polyurethane with antistatic surface can reach 2.3×10 8 Ω, reaching anti-static level and having long-term durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermoplastic polyurethane elastomers, and in particular relates to a method for preparing thermoplastic polyurethane with antistatic properties on the surface. Background Art

[0002] Thermoplastic polyurethane (TPU) is a polyurethane material with excellent physical and chemical properties. It has high strength, high toughness, high elasticity, chemical corrosion resistance, good wear resistance and excellent shock resistance. In the production process, its hardness, density, elastic modulus and other properties can be adjusted by adjusting the raw material ratio and process parameters. It is widely used in the industrial field. However, thermoplastic polyurethane has a high surface resistivity (10 11 ~10 14 Ω) and volume resistivity (10 13 ~10 15 Ω·m), which is an insulating material. In use, there is often static electricity hazard caused by charge accumulation due to surface friction. Therefore, thermoplastic polyurethane needs to be treated with antistatic modification.

[0003] According to the different ways of using antistatic agents, they can be divided into internal addition type and external coating type. The internal addition type mainly uses graphite, metal, metal oxide and ionic liquid antistatic agents. For example, Chinese invention patent CN 101743262 B uses ethylmethylimidazole ethyl sulfate and thermoplastic polyurethane blending to carry out antistatic modification, but the amount of addition is large. Chinese invention patent CN 108178827 B adds modified graphene to improve antistatic performance when synthesizing thermoplastic polyurethane, and this method will produce color changes. The commonly used antistatic agent for external coating type is quaternary ammonium salt surfactant, which adopts coating or impregnation to make the material surface have antistatic properties. The process is simple, easy to operate, and is not limited by the shape of TPU products, but the antistatic agent on the surface of the product will disappear due to friction and washing, and the durability is poor. Summary of the invention

[0004] In view of the deficiencies of the above-mentioned prior art, the present invention provides a method for preparing thermoplastic polyurethane with antistatic surface. The specific technical scheme is as follows:

[0005] A method for preparing thermoplastic polyurethane with antistatic surface comprises the following steps:

[0006] (1) By weight percentage, a polyester diol containing a double bond structure: 35% to 70%; a diisocyanate: 25% to 55%; a chain extender: 2% to 15%; a catalyst: 0.001% to 0.05%; an antioxidant: 0.1% to 0.3%; and a light stabilizer: 0.1% to 0.3% are prepared into a thermoplastic polyurethane product;

[0007] (2) Immersing the thermoplastic polyurethane product of step (1) in an aqueous solution containing a photoinitiator and an antistatic agent, and performing surface antistatic treatment by UV irradiation, wherein the photoinitiator is a water-soluble photoinitiator that initiates a reaction under UV light; and the antistatic agent contains a thiol functional group.

[0008] The present invention adopts polyester diol containing a double bond structure to prepare a thermoplastic polyurethane elastomer containing a double bond, and then performs surface antistatic treatment to prepare a thermoplastic polyurethane with longer-lasting surface antistatic durability. During the surface antistatic treatment, UV light first causes a photoinitiator to react, and then the photoinitiator induces a thiol group on the antistatic agent and a double bond of the thermoplastic polyurethane to undergo an addition reaction, and the antistatic agent is connected to the polyurethane by a chemical reaction, so as to avoid the antistatic agent from escaping due to friction, washing, etc., and the antistatic effect can be maintained for a longer period of time.

[0009] Furthermore, the side chain of the polyester diol containing a double bond structure contains a double bond structure.

[0010] Furthermore, the polyester diol containing a double bond structure is obtained by condensation polymerization of a dicarboxylic acid and a diol, the molar ratio of the dicarboxylic acid to the diol is 1:(1.01-1.5), the dicarboxylic acid includes a dicarboxylic acid containing a double bond structure and a dicarboxylic acid not containing a double bond structure, and the mass fraction of the dicarboxylic acid containing a double bond structure is 5%-10% of the total mass of the dicarboxylic acid.

[0011] By mixing a small amount of dicarboxylic acids with double bond structures in the side chains and dicarboxylic acids without double bond structures, the structural regularity of the obtained polyester diol can be maintained as much as possible, and the mechanical properties of the thermoplastic polyurethane can be maintained. The double bonds in the side chains can provide active sites for antistatic surface treatment, making the reaction of the surface antistatic agent easier to proceed.

[0012] Furthermore, the preparation method of the polyester diol containing a double bond structure is as follows: under nitrogen protection, a dicarboxylic acid, a diol and a polyester synthesis catalyst are mixed, the temperature is raised to 140-190° C., and the reaction is carried out at a constant temperature for 1-5 hours; then the temperature is continued to be raised to 200-220° C. within 0.5-2.5 hours, and vacuum is turned on when the acid value is lower than 5 mgKOH / g to remove moisture and small molecular alcohols in the system, and the reaction is continued until the hydroxyl value is 20-100 mgKOH / g and the acid value is 0.15-0.40 mgKOH / g, thereby obtaining a polyester diol containing a double bond structure.

[0013] Furthermore, the dicarboxylic acid without a double bond structure is one or more of malonic acid, 2-methylmalonic acid, 1,4-succinic acid, 1,5-pentanedioic acid, 2-methyl-1,4-succinic acid, 2,2-dimethyl-1,3-malonic acid, 1,6-hexanedioic acid, α-methylglutaric acid, β-methylglutaric acid, α-ethylsuccinic acid, α-(dimethyl)succinic acid, α,β-(dimethyl)succinic acid, n-propylmalonic acid, 1,7-pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, dimer acid, terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, 1,3-cyclobutane dicarboxylic acid, and 1,1-cyclobutane dicarboxylic acid.

[0014] Furthermore, the dicarboxylic acid containing a double bond structure is one or more of 2-methylenemalonic acid, 2-methylenesuccinic acid, 2-methyleneglutaric acid, and 2-methyl-5-methyleneadipic acid.

[0015] Further, the diol is one or more of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,2-butanediol, 1,3-butanediol, 1,2-pentanediol, 1,5-pentanediol, 2,5-dimethyl-2,5-hexanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 2-methyl-1,3-propylene glycol, 2,2-dimethyl-1,3-propylene glycol, 3-methyl-1,5-pentanediol, dipropylene glycol, and diethylene glycol.

[0016] Furthermore, the polyester synthesis catalyst is one of tetraisobutyl titanate, zinc acetate, and antimony trioxide, preferably tetraisopropyl titanate.

[0017] Furthermore, the isocyanate index of the thermoplastic polyurethane is 0.95 to 1.05.

[0018] Furthermore, the method for preparing the thermoplastic polyurethane product comprises the following steps:

[0019] The diisocyanate compound is heated and melted, and a polyester diol containing a double bond structure, a catalyst, an antioxidant and a light stabilizer are added, and the reaction is carried out at 60-110°C for 0.5-4 hours to generate a prepolymer; then a chain extender is added, the chain extender and the prepolymer are mixed evenly, and ripened at 90-130°C for 8-24 hours to obtain a thermoplastic polyurethane elastomer, which is then crushed and processed into a thermoplastic polyurethane product by injection molding or extrusion.

[0020] Furthermore, the photoinitiator is one or more of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (Iragcure 2959), 1-hydroxycyclohexyl phenyl ketone (Irgacure184), 2-hydroxy-1-[3-(hydroxymethyl)phenyl]-2-methyl-1-propanone (APi-180), 3-(4-benzylphenoxy)-2-hydroxy-N,N,N-trimethyl-1-propylamine chloride (Q-BPQ), and 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide) (VA-086).

[0021] Furthermore, the antistatic agent is one or more of mercapto polyethylene glycol, 3-mercapto-1-propanesulfonic acid sodium salt, and mercaptoethylamine hydrochloride.

[0022] The thiol functional group of the antistatic agent can react with double bonds, and the thiol polyethylene glycol is hygroscopic and can absorb moisture in the air to increase conductivity; 3-mercapto-1-propanesulfonic acid sodium salt and mercaptoethylamine hydrochloride are ionic compounds that increase conductivity in an ionic manner, and increasing conductivity can increase antistatic properties.

[0023] Furthermore, the mass percentage concentration ratio of the photoinitiator and the antistatic agent in the aqueous solution is 1:(5-10).

[0024] Furthermore, the concentration of the photoinitiator is 0.001-0.1 g / ml.

[0025] Furthermore, the diisocyanate is diphenylmethane-4,4'-diisocyanate (MDI); the chain extender is 1,4-butanediol; the catalyst is dibutyltin dilaurate (DBTDL); the antioxidant is Irganox 1076; and the light stabilizer is Tinuvin 326.

[0026] Furthermore, the UV irradiation duration is 0.5 to 2 hours.

[0027] The beneficial effects of the present invention are:

[0028] The present invention adopts polyester diol containing double bond structure to prepare thermoplastic polyurethane elastomer containing double bond, and then prepares thermoplastic polyurethane with surface antistatic by surface antistatic treatment, so as to achieve the purpose of surface antistatic modification. The surface resistivity of the thermoplastic polyurethane with surface antistatic can reach 2.3×10 8 Ω, reaching anti-static level and having long-term durability. DETAILED DESCRIPTION

[0029] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0030] Embodiment 1:

[0031] Preparation of polyester diol A containing double bond structure:

[0032] Under nitrogen protection, 6.800 mol of adipic acid, 0.054 mol of 2-methylenemalonic acid, 8.255 mol of 1,4-butanediol and 0.0013 mol of tetraisopropyl titanate catalyst were added to a 5L reactor in sequence, the temperature was raised to 160°C, and the reaction was carried out at a constant temperature for 4 hours. The temperature was then further raised to 200°C within 0.5 hours. When the acid value was lower than 5 mgKOH / g, the vacuum was turned on to remove the moisture and small molecular alcohol in the system. The reaction was continued until the hydroxyl value was 56.0 mgKOH / g and the acid value was 0.26 mgKOH / g. The temperature was lowered and the material was discharged to obtain polyester diol A containing a double bond structure with a moisture content of 73 ppm.

[0033] Preparation of Thermoplastic Polyurethane Test Piece A:

[0034] 630.00g of diisocyanate MDI was heated and melted, and 1187.60g of polyester diol A containing a double bond structure, 0.20g of catalyst dibutyltin dilaurate, 6.0g of antioxidant Irganox 1076 (BASF (China) Co., Ltd.) and 6.0g of light stabilizer Tinuvin 326 (BASF (China) Co., Ltd.) were added, and reacted at a temperature of 90°C for 3h to generate a prepolymer; then 170.20g of chain extender 1,4-butanediol was added and mixed evenly with the prepolymer, and aged at 95°C for 12h to obtain thermoplastic polyurethane elastomer A, and then the obtained thermoplastic polyurethane elastomer A was sliced ​​and crushed and injection molded into 2mm thick thermoplastic polyurethane test piece A.

[0035] Surface antistatic treatment:

[0036] The thermoplastic polyurethane test piece A obtained by injection molding was immersed in an aqueous solution containing a photoinitiator Iragcure 2959 and an antistatic agent mercapto polyethylene glycol, wherein the concentration of the photoinitiator Iragcure 2959 was 0.005 g / ml and the concentration of the antistatic agent mercapto polyethylene glycol was 0.05 g / ml. The test piece was treated with UV light for 1 hour, washed with deionized water and dried at room temperature to obtain a thermoplastic polyurethane sample A with antistatic surface.

[0037] Embodiment 2:

[0038] Preparation of polyester diol B containing double bond structure:

[0039] Under nitrogen protection, 6.800 mol of adipic acid, 0.048 mol of 2-methylenebutanedioic acid, 8.218 mol of 1,4-butanediol and 0.0014 mol of tetraisopropyl titanate catalyst were added to a 5L reactor in sequence, the temperature was raised to 160°C, and the reaction was carried out at a constant temperature for 4 hours. The temperature was then further raised to 200°C within 0.5 hours. When the acid value was lower than 5 mgKOH / g, the vacuum was turned on to remove the moisture and small molecular alcohol in the system. The reaction was continued until the hydroxyl value was 56.2 mgKOH / g, the acid value was 0.31 mgKOH / g, and the moisture content was 107 ppm. The temperature was lowered and the material was discharged to obtain polyester diol B containing a double bond structure.

[0040] Preparation of Thermoplastic Polyurethane Test Piece B:

[0041] 629.40g of diisocyanate MDI was heated and melted, and 1187.80g of polyester diol B containing a double bond structure, 0.20g of catalyst dibutyltin dilaurate, 6.0g of antioxidant Irganox 1076 (BASF (China) Co., Ltd.) and 6.0g of light stabilizer Tinuvin 326 (BASF (China) Co., Ltd.) were added, and the mixture was reacted at 90°C for 3h to generate a prepolymer; 170.60g of chain extender 1,4-butanediol was added and mixed evenly with the prepolymer, and aged at 95°C for 12h to obtain a thermoplastic polyurethane elastomer B, and then the obtained thermoplastic polyurethane elastomer B was sliced ​​and crushed and injection molded into a 2mm thick thermoplastic polyurethane test piece B.

[0042] Surface antistatic treatment:

[0043] The steps are the same as those in Example 1 and will not be repeated here to obtain a thermoplastic polyurethane sample B-1 with antistatic surface.

[0044] Embodiment 3:

[0045] Preparation of polyester diol C containing double bond structure:

[0046] Under nitrogen protection, 6.800 mol of adipic acid, 0.043 mol of 2-methyleneglutaric acid, 8.212 mol of 1,4-butanediol and 0.0013 mol of tetraisopropyl titanate catalyst were added to a 5L reactor in sequence, the temperature was raised to 160°C, and the reaction was carried out at a constant temperature for 4 hours. Then, the temperature was further raised to 200°C within 0.5 hours. When the acid value was lower than 5 mgKOH / g, vacuum was turned on to remove moisture and small molecular alcohols in the system. The reaction was continued until the hydroxyl value was 56.3 mgKOH / g, the acid value was 0.24 mgKOH / g, and the moisture content was 87 ppm. The temperature was lowered and the material was discharged to obtain polyester diol C containing a double bond structure.

[0047] Preparation of Thermoplastic Polyurethane Test Piece C:

[0048] 669.80 g of diisocyanate MDI was heated and melted, and 1147.80 g of polyester diol C containing a double bond structure, 0.20 g of catalyst dibutyltin dilaurate, 6.0 g of antioxidant Irganox 1076 (BASF (China) Co., Ltd.) and 6.0 g of light stabilizer Tinuvin 326 (BASF (China) Co., Ltd.) were added, and the mixture was reacted at 90°C for 3 hours to generate a prepolymer; 170.20 g of chain extender 1,4-butanediol was added and mixed evenly with the prepolymer, and aged at 95°C for 12 hours to obtain a thermoplastic polyurethane elastomer C, and then the obtained thermoplastic polyurethane elastomer C was sliced ​​and crushed and injection molded into a 2 mm thick thermoplastic polyurethane test piece C.

[0049] Surface antistatic treatment:

[0050] The steps are the same as those in Example 1 and will not be repeated here to obtain a thermoplastic polyurethane sample C with antistatic surface.

[0051] Embodiment 4:

[0052] Preparation of polyester diol D containing double bond structure:

[0053] Under nitrogen protection, 6.800 mol of adipic acid, 0.036 mol of 2-methyl-5-methylene adipic acid, 8.203 mol of 1,4-butanediol and 0.0015 mol of tetraisopropyl titanate catalyst were added to a 5L reactor in sequence, the temperature was raised to 160°C, and the reaction was carried out at a constant temperature for 4 hours. The temperature was then further raised to 200°C within 0.5 hours. When the reaction was carried out until the acid value was lower than 5 mgKOH / g, vacuum was turned on to remove moisture and small molecular alcohols in the system. The reaction was continued until the hydroxyl value was 56.1 mgKOH / g, the acid value was 0.29 mgKOH / g, and the moisture content was 91 ppm. The temperature was then lowered and the material was discharged to obtain polyester diol D containing a double bond structure.

[0054] Preparation of Thermoplastic Polyurethane Test Piece D:

[0055] 662.80 g of diisocyanate MDI was heated and melted, and 1157.60 g of polyester diol D containing a double bond structure, 0.40 g of catalyst dibutyltin dilaurate, 6.0 g of antioxidant Irganox 1076 (BASF (China) Co., Ltd.) and 6.0 g of light stabilizer Tinuvin 326 (BASF (China) Co., Ltd.) were added, and reacted at a temperature of 90°C for 3 hours to generate a prepolymer; then 167.20 g of chain extender 1,4-butanediol was added and mixed evenly with the prepolymer, and aged at 95°C for 12 hours to obtain a thermoplastic polyurethane elastomer D, and then the obtained thermoplastic polyurethane elastomer D was sliced ​​and crushed and injection molded into a 2 mm thick thermoplastic polyurethane test piece D.

[0056] Surface antistatic treatment:

[0057] The steps are the same as those in Example 1 and will not be repeated here to obtain a thermoplastic polyurethane sample D with antistatic surface.

[0058] Embodiment 5:

[0059] Thermoplastic polyurethane test piece B was prepared using the same method and steps as in Example 2, which will not be described in detail herein.

[0060] Surface antistatic treatment:

[0061] The thermoplastic polyurethane test piece B obtained by injection molding was immersed in an aqueous solution containing a photoinitiator Iragcure 2959 and an antistatic agent 3-mercapto-1-propanesulfonic acid sodium salt, wherein the concentration of the photoinitiator Iragcure 2959 was 0.005 g / ml and the concentration of the antistatic agent 3-mercapto-1-propanesulfonic acid sodium salt was 0.045 g / ml. The test piece was treated with UV light for 1 hour, washed with deionized water and dried at room temperature to obtain a thermoplastic polyurethane sample B-2 with antistatic surface.

[0062] Embodiment 6:

[0063] Thermoplastic polyurethane test piece B was prepared using the same method and steps as in Example 2, which will not be described in detail herein.

[0064] Surface antistatic treatment:

[0065] The thermoplastic polyurethane test piece B obtained by injection molding was immersed in an aqueous solution containing a photoinitiator Iragcure 184 and an antistatic agent 3-mercapto-1-propanesulfonic acid sodium salt, wherein the concentration of the photoinitiator Iragcure 184 was 0.001 g / ml and the concentration of the antistatic agent 3-mercapto-1-propanesulfonic acid sodium salt was 0.01 g / ml. The test piece was treated with UV light for 1 hour, washed with deionized water and dried at room temperature to obtain a thermoplastic polyurethane sample B-3 with antistatic surface.

[0066] Embodiment 7:

[0067] Thermoplastic polyurethane test piece B was prepared using the same method and steps as in Example 2, which will not be described in detail herein.

[0068] Surface antistatic treatment:

[0069] The thermoplastic polyurethane test piece B obtained by injection molding was immersed in an aqueous solution containing a photoinitiator APi-180 and an antistatic agent mercaptoethylamine hydrochloride, wherein the concentration of the photoinitiator APi-180 was 0.065 g / ml and the concentration of the antistatic agent mercaptoethylamine hydrochloride was 0.455 g / ml. The test piece was treated with UV light for 1 hour, washed with deionized water and dried at room temperature to obtain a thermoplastic polyurethane sample B-4 with antistatic surface.

[0070] Comparative Example 1:

[0071] Preparation of Thermoplastic Polyurethane Test Piece E:

[0072] 633.60g of diisocyanate MDI was heated and melted, and 1182.40g of PBA2000, 0.20g of catalyst dibutyltin dilaurate, 6.0g of antioxidant Irganox 1076 (BASF (China) Co., Ltd.) and 6.0g of light stabilizer Tinuvin 326 (BASF (China) Co., Ltd.) were added, and reacted at a temperature of 90°C for 3h to generate a prepolymer; then 171.80g of chain extender 1,4-butanediol was added and mixed evenly with the prepolymer, and aged at 95°C for 12h to obtain thermoplastic polyurethane elastomer E, and then the obtained thermoplastic polyurethane elastomer E was sliced ​​and crushed and injection molded into 2mm thick thermoplastic polyurethane test piece E.

[0073] Surface physical coating antistatic treatment:

[0074] The thermoplastic polyurethane specimen E was immersed in an aqueous solution containing an antistatic agent, stearamidopropyl dimethyl-β-hydroxyethyl ammonium nitrate (Cyastat SN), immersed for 1 hour and then dried at room temperature to obtain a thermoplastic polyurethane sample E.

[0075] Comparative Example 2:

[0076] Preparation of Thermoplastic Polyurethane Test Piece F:

[0077] 661.80 g of diisocyanate MDI was heated and melted, and 1142.20 g of PTMG2000, 0.20 g of catalyst dibutyltin dilaurate, 6.0 g of antioxidant Irganox 1076 (BASF (China) Co., Ltd.) and 6.0 g of light stabilizer Tinuvin 326 (BASF (China) Co., Ltd.) were added, and reacted at a temperature of 90°C for 3 hours to generate a prepolymer; then 183.80 g of chain extender 1,4-butanediol was added and mixed evenly with the prepolymer, and aged at 95°C for 12 hours to obtain a thermoplastic polyurethane elastomer F, and then the obtained thermoplastic polyurethane elastomer F was sliced ​​and crushed and injection molded into a 2 mm thick thermoplastic polyurethane test piece F.

[0078] Surface physical coating antistatic treatment:

[0079] The thermoplastic polyurethane specimen F was immersed in an aqueous solution containing an antistatic agent (3-laurylamidopropyl)trimethylammonium methyl sulfate (Cyastat-LS), immersed for 1 hour and then dried at room temperature to obtain a thermoplastic polyurethane sample F.

[0080] The dried samples obtained from each embodiment and comparative example were tested for surface resistivity after treatment, surface resistivity after 3 months, and surface resistivity after 6 months.

[0081] Test method: The surface resistivity was tested according to ASTM D257-14 “Standard Test Methods for DC Resistance or Conductance of Insulating Materials”. The test results are shown in Table 1.

[0082] Table 1 Surface resistivity test results of samples of various embodiments and comparative examples

[0083]

[0084] It can be seen from the experimental data of each embodiment and comparative example in Table 1 that the present invention can achieve a surface antistatic effect by preparing a thermoplastic polyurethane elastomer containing double bonds and then preparing a surface antistatic thermoplastic polyurethane through a surface antistatic treatment process. Compared with the surface physical coating type antistatic treatment process, it has long-term durability.

[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a thermoplastic polyurethane with antistatic surface, characterized in that: The steps include: (1) By weight percentage, the following components are prepared into a thermoplastic polyurethane product: 35% to 70% polyester diol containing a double bond structure; 25% to 55% diisocyanate; 2% to 15% chain extender; 0.001% to 0.05% catalyst; 0.1% to 0.3% antioxidant; and 0.1% to 0.3% light stabilizer; (2) immersing the thermoplastic polyurethane product of step (1) in an aqueous solution containing a photoinitiator and an antistatic agent, and performing surface antistatic treatment by UV irradiation, wherein the photoinitiator is a water-soluble photoinitiator that initiates a reaction under UV light; The antistatic agent is one or more of mercapto polyethylene glycol, 3-mercapto-1-propanesulfonic acid sodium salt, and mercaptoethylamine hydrochloride; The polyester diol containing a double bond structure is obtained by condensation polymerization of a dicarboxylic acid and a diol, the molar ratio of the dicarboxylic acid to the diol is 1:(1.01-1.5), the dicarboxylic acid includes a dicarboxylic acid containing a double bond structure and a dicarboxylic acid not containing a double bond structure, and the mass fraction of the dicarboxylic acid containing a double bond structure is 5%-10% of the total mass of the dicarboxylic acid.

2. The method for preparing the surface antistatic thermoplastic polyurethane according to claim 1, characterized in that: The side chain of the polyester diol containing a double bond structure contains a double bond structure.

3. The method for preparing the surface antistatic thermoplastic polyurethane according to claim 1, characterized in that: The preparation method of the thermoplastic polyurethane product comprises the following steps: The diisocyanate compound is heated and melted, and a polyester diol containing a double bond structure, a catalyst, an antioxidant and a light stabilizer are added, and the reaction is carried out at 60-110°C for 0.5-4 hours to generate a prepolymer; then a chain extender is added, the chain extender and the prepolymer are mixed evenly, and ripened at 90-130°C for 8-24 hours to obtain a thermoplastic polyurethane elastomer, which is then crushed and processed into a thermoplastic polyurethane product by injection molding or extrusion.

4. The method for preparing the surface antistatic thermoplastic polyurethane according to claim 1, characterized in that: The photoinitiator is one or more of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 1-hydroxycyclohexyl phenyl ketone, and 2,2'-azo (2-methyl-N-(2-hydroxyethyl) propionamide).

5. The method for preparing the surface antistatic thermoplastic polyurethane according to claim 1, characterized in that: The mass percentage concentration ratio of the photoinitiator to the antistatic agent in the aqueous solution is 1:(5-10).

6. The method for preparing the surface antistatic thermoplastic polyurethane according to claim 1, characterized in that: The UV irradiation duration is 0.5 to 2 hours.

7. The method for preparing the surface antistatic thermoplastic polyurethane according to claim 1, characterized in that: The diisocyanate is diphenylmethane-4,4'-diisocyanate; the chain extender is 1,4-butanediol; the catalyst is dibutyltin dilaurate; the antioxidant is Irganox 1076; and the light stabilizer is Tinuvin 326.

8. The method for preparing the surface antistatic thermoplastic polyurethane according to claim 1, characterized in that: The dicarboxylic acid without double bond structure is one or more of malonic acid, 2-methylmalonic acid, 1,4-succinic acid, 1,5-glutaric acid, 2-methyl-1,4-succinic acid, 2,2-dimethyl-1,3-malonic acid, 1,6-hexanedioic acid, α-methylglutaric acid, β-methylglutaric acid, α-ethylsuccinic acid, α-(dimethyl)succinic acid, α,β-(dimethyl)succinic acid, n-propylmalonic acid, 1,7-pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, dimer acid, terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, 1,3-cyclobutane dicarboxylic acid, and 1,1-cyclobutane dicarboxylic acid; The dicarboxylic acid containing a double bond structure is one or more of 2-methylenemalonic acid, 2-methylenesuccinic acid, 2-methyleneglutaric acid, and 2-methyl-5-methyleneadipic acid; The diol is one or more of ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,2-pentanediol, 1,5-pentanediol, 2,5-dimethyl-2,5-hexanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 2-methyl-1,3-propylene glycol, 2,2-dimethyl-1,3-propylene glycol, 3-methyl-1,5-pentanediol, dipropylene glycol, and diethylene glycol.

Citation Information

Patent Citations

  • Thermoplastic polyurethane with antistatic properties

    CN101743262B

  • Antistatic polyurethane elastomer and its preparation method

    CN108178827B

  • Antistatic flexible polyurea composition, preparation thereof, construction method and applications

    CN101338017A

  • Antistatic thermoplastic polyurethane as well as preparation method and application thereof

    CN115873395A